2007
DOI: 10.1109/tpami.2007.1102
|View full text |Cite
|
Sign up to set email alerts
|

Nonsmooth Optimization Techniques for Semisupervised Classification

Abstract: We apply nonsmooth optimization techniques to classification problems, with particular reference to the TSVM (Transductive Support Vector Machine) approach, where the considered decision function is nonconvex and nondifferentiable and then difficult to minimize.We present some numerical results obtained by running the proposed method on some standard test problems drawn from the binary classification literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 23 publications
(18 reference statements)
0
30
0
Order By: Relevance
“…Nonsmooth optimization models of unsupervised and supervised data classification problems are also discussed in [4,5,23].…”
Section: Comparison Of Different Formulations Of Clustering Problemmentioning
confidence: 99%
“…Nonsmooth optimization models of unsupervised and supervised data classification problems are also discussed in [4,5,23].…”
Section: Comparison Of Different Formulations Of Clustering Problemmentioning
confidence: 99%
“…As proposed there, we can apply a gradient descent based technique, either relying on subgradients [3] or smoothing the objective function first, e.g. by a softmax operation.…”
Section: Optimization By Gradient Descent In the Primalmentioning
confidence: 99%
“…(Vapnik, 1998) based on their unlabeled sets under the exactly same setting as theirs. Note that the datasets for g50c and g10n were given in Chapelle and Zien (2005) whereas those of Heart and Ionosphere were sampled at random according to Astorino and Fuduli (2005). Table 3 indicates that TSVM DCA outperforms ∇TSVM in all the cases, while outperforming TSVM Bundle in all cases except g50c.…”
Section: Generalization Performancementioning
confidence: 99%
“…Chapelle and Zien (2005) suggested that the cost function of TSVM is appropriate but implementation of TSVM is inadequate. Astorino and Fuduli (2005) also noted that implementation of TSVM is an issue.…”
Section: Introductionmentioning
confidence: 99%